Analysis of Volatiles of Rose Pepper Fruits by GC/MS: Drying Kinetics, Essential Oil Yield, and External Color Analysis - Kênia Borges de Oliveira; Marcio Carocho; Tiane Finimundy; Osvaldo Resende; Juliana Aparecida Célia; Francileni Pompeu Gomes; Wellytton Darci Quequeto; Fabiano José de Campos Bastos; Lillian Barros; Weder Nunes Ferreira Junior (Journal of Food Quality)
Condiments and culinary supplements are subjected to long-term storage and may undergo physical, chemical, and biological changes that can influence their quality. Thus, the objective of the present study was to analyze the drying kinetics of rose pepper (Schinus terebinthifolius Raddi) fruits in an oven with forced air circulation at different temperatures, namely, 45, 55, 65, and 75°C, and determine the effective diffusion coefficient and activation energy using different mathematical models. Furthermore, the effects of the different drying temperatures were analyzed for external color parameters and yield of essential oil contents by gas chromatography coupled to a mass spectrometer. Of the ten models used for fitting, Thompson’s model was one with the best fitting to represent the drying of rose pepper fruits. The diffusion coefficient increases with the elevation of drying air temperature, described by the Arrhenius equation, with activation energy of 53.579 kJ·mol−1. The color of the fruits decreased in lightness (L∗) with the increase in temperature. Of the thirty-eight terpenes identified, α-pinene and cis-ocimene were the most abundant, with the overall highest yield being found at a drying temperature of 45°C.